Solvent motion in quaternary reverse micelles - Corbeil, Elizabeth M., author (Colorado State University. Libraries, 2004)
The solvation response in CTAB and SDS reverse micelles has been investigated via ultrafast time-resolved fluorescence spectroscopy. These measurements represent the first determination of solvation reorganization on the subpicsecond timescale in quaternary micellar systems. These experiments provide insight on the solvent motion in quaternary reverse micelles and are compared to bulk water relaxation on a femtosecond timescale. The solvent response in CTAB and SDS reverse micelles was measured as a function of hydration. Solvent reorganization was found to be independent of hydration. In all of the systems investigated, two solvent relaxation components are observed, specifically an inertial component on the femtosecond timescale as well as a diffusive component on the order of hundreds of picoseconds. These relaxation components were attributed to collective motion of the interface. To explore the role of the cosurfactant, we explored solvent motion in ternary and quaternary AOT reverse micelles. The addition of alkanol significantly slows down solvent motion in the micellar systems. The solvent response in quaternary AOT reverse micelles also had a diffusive component that was similar to that found in CTAB and SDS reverse micelles.
Keywords: chemistry; physical chemistry